2020
DOI: 10.1001/jama.2020.11301
|View full text |Cite
|
Sign up to set email alerts
|

Association of Angiotensin-Converting Enzyme Inhibitor or Angiotensin Receptor Blocker Use With COVID-19 Diagnosis and Mortality

Abstract: IMPORTANCE It has been hypothesized that angiotensin-converting enzyme inhibitors (ACEIs)/angiotensin receptor blockers (ARBs) may make patients more susceptible to coronavirus disease 2019 and to worse outcomes through upregulation of the functional receptor of the virus, angiotensin-converting enzyme 2.OBJECTIVE To examine whether use of ACEI/ARBs was associated with COVID-19 diagnosis and worse outcomes in patients with COVID-19. DESIGN, SETTING, AND PARTICIPANTSTo examine outcomes among patients with COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
405
6
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(452 citation statements)
references
References 37 publications
23
405
6
12
Order By: Relevance
“…By early April 2020, a few pharmacological interventions were available mostly within the frame of clinical trials [28], which, alongside with improved clinical management, could have had an impact on our outcome estimates over time. In comparison to previous studies from Denmark [5][6][7] we found a higher mortality. However, we report outcomes in a selected group of patients namely those in need of hospitalisation and therefore presenting with a more severe clinical course.…”
Section: Study Strengths and Limitationscontrasting
confidence: 95%
See 2 more Smart Citations
“…By early April 2020, a few pharmacological interventions were available mostly within the frame of clinical trials [28], which, alongside with improved clinical management, could have had an impact on our outcome estimates over time. In comparison to previous studies from Denmark [5][6][7] we found a higher mortality. However, we report outcomes in a selected group of patients namely those in need of hospitalisation and therefore presenting with a more severe clinical course.…”
Section: Study Strengths and Limitationscontrasting
confidence: 95%
“…The rst case in Denmark was diagnosed on February 27th, 2020, and during the rst month, the number of laboratory-con rmed cases rose to more than 3,000; 500 patients were hospitalised, of which 30% required admission to an intensive care unit (ICU) and 5% died Despite variations reported across countries, emerging evidence consistently indicates that older men with multiple comorbidities have poorer COVID-19-related outcomes [2][3][4]. To date, studies from Denmark focusing on the overall epidemiological characteristics during the early phase of the epidemic (until May 2020) [5,6] and the association with several cardiovascular outcomes have been made publicly available [7]. From these early reports, COVID-19 related mortality in Denmark have been described to vary between 9.3-16.6% and rates of ICU admission between 12.9-17.8% depending on the speci c groups of patients studied [5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the main scientific societies of cardiology and more specifically of hypertension took the position not to withdraw ACEi or ARB therapy in COVID‐19. Hence, the Council on Hypertension of the European Society of Cardiology recommended that "patients should continue treatment with their usual anti‐hypertensive therapy because there is no clinical or scientific evidence to suggest that treatment with ACEIs or ARBs should be discontinued because of the COVID‐19 infection.” 33 Indeed, recent studies did not find any association between ACEi or ARBs therapy and worsening in COVID‐19 patients 34 …”
Section: Discussionmentioning
confidence: 98%
“…The lower prevalence of ACE inhibitor intake among COVID-19 seropositive patients does not support the hypothesis that these molecules could make patients more susceptible to SARS-Cov2 infection. However, literature data still remains controversial [25,26].…”
Section: Discussionmentioning
confidence: 99%